The effects of Baduanjin and yoga exercise programs on physical and mental health in patients with Multiple Sclerosis: A randomized controlled trial - Yuchen Pan; Yong Huang; Hui Zhang; Yuanjie Tang; Cunjin Wang (Elsevier, 2022)
Objective: To discuss whether Baduanjin and yoga exercise interventions improve motor function, posture control, and relieving fatigue and depression in MS patients. And to explore whether practicing Baduanjin benefits MS patients more than yoga. Design: A prospective, randomized, controlled, three-arm trial comparing BDJ (n = 30), yoga (n = 30) and control group (n = 20). Setting: Jiangsu Provincial Corps Hospital. Intervention: Eligible participants were randomized to a 24-week Baduanjin or yoga intervention, or a usual activity control group. Balance, posture control and trunk movement were measured with the Berg Balance Scale (BBS) and Trunk Impairment Scale (TIS). Fatigue was measured using the Fatigue Severity Scale (FSS) and depressive symptoms via the Zung Self-Rating Depression Scale (SDS). Results: For BBS and TIS, there were significant changes pre- to post- exercise in two exercise groups (P < 0.05), with greater increases in the Baduanjin exercise group (BDJ group). For the FSS, there were significant changes pre- to post- exercise in both the BDJ (P = 0.0292) and yoga groups (P = 0.0150). For the SDS, the pre- and post-exercise difference of the BDJ group was larger than the yoga group (P < 0.0001). On the other hand, we could not find any changes of the BBS, TIS, FSS, and SDS scores in the control group (p > 0.05). Conclusion: The results suggest that practicing Baduanjin was more effective than yoga and that it is suitable for the MS patients.